(untitled) (Malaysian Management Journal, 2005)
It is argued that countries, which adopt an open economic policy, enjoy faster economic growth than countries which do not, suggesting that "trade openness" can spur economic growth. However, the issue is whether the positive impact of trade openness to economic growth varies across countries. Hence, the objective of this paper is to determine whether the effect of openness to trade on economic growth varies across the region in Asia. To achieve this objective, panel data regressions were employed to estimate the growth equation. Empirical results indicated that "trade openness" does have a positive effect on economic growth and the marginal benefit from improved openness is somewhat higher for East Asian Economies relative to other Asian economies.